The bifurcation level and geometric anatomy of abdominal aorta – Does it matter in cervical malignancy? Experience from tertiary cancer center (Asian Journal of Medical Sciences, 2024)
Background: The course, the origin of the branch, and the division of the aorta may vary and the aortic bifurcation level and branching can be determined by arteriogram, magnetic resonance imaging, computed tomography (CT) scan, and cadaveric dissection.Aims and Objectives: This study aimed to find the variation in aortic bifurcation levels in cervical malignancy patients who underwent radiotherapy.Materials and Methods: Between January 2018 and December 2022 previously untreated, histologically proven squamous cell carcinoma of the cervix patients who received radiotherapy in our department were selected for this retrospective analysis. A planning contrast-enhanced CT scan with a 3 mm slice thickness was done in a CT simulator to delineate the target volume and aorta, common iliac vessels in all patients.Results: 407 cervical carcinoma patients who received radiotherapy in Linear Accelerator (LINAC) were included in this analysis. The aortic bifurcation is most commonly situated at the level of the L3–L4 intervertebral disc in 290 (71.25%) cases with a range between the upper L3 body and the lower L5 body. The common iliac bifurcation was situated at the level of L5–S1 in 338 cases (83.04%) and S1 vertebral body in 63 cases (15.47%). The average length of the left common iliac artery was 4.58 cm and the right common iliac artery was 4.44 cm. The diameter of the aorta at the level of just before the bifurcation is 1.39 cm. The average diameter of the left common iliac artery and right common iliac artery were 1.21 cm and 1.13 cm, respectively. The right and left take-off angles (αR, αL) are 25.58° and 23.78°, respectively.Conclusion: The knowledge regarding the anatomic variation of branching and bifurcation of the aorta of utmost importance for surgical procedures, interventional radiology procedures, and proper radiotherapy treatment planning. Acknowledging these anatomic variations may also reduce complications.